2021
DOI: 10.5114/polp.2021.112395
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease (NAFLD) spectrum in children with type 1 diabetes mellitus evaluated with non-invasive fibrosis score and instrument: A cross-sectional study

Abstract: The aim of the study was to evaluate NAFLD spectrum in children with type 1 of diabetes mellitus (T1DM) by simple fibrosis scores and advanced biochemical markers in association with abdominal ultrasonography (US), Acoustic radiation force impulse elastography (ARFI) and comparing their results. Material and methods: A case-control study was conducted on 142children and adolescents with T1DM and79 subjects as controls. Through medical history, clinical examination, and laboratory assessment including glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Whereas, Al-Hussaini et al detected hepatic affection in 10% of 106 children with type 1 diabetes in an Indian study [ 25 ], and El-Karaksy et al (a larger study of 692 Egyptian children with type 1 diabetes) declared a prevalence of 4.5% of liver affection [ 26 ]. On the other hand, Farhan et al, reported abnormal hepatic findings in (26%) of children with type 1 diabetes [ 7 ] and ElBaki et al in their study detected 37.3% of cases with NAFLD [ 27 ] . The high prevalence of hepatic affection in our study could be attributed to poorer glycemic control of the included patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, Al-Hussaini et al detected hepatic affection in 10% of 106 children with type 1 diabetes in an Indian study [ 25 ], and El-Karaksy et al (a larger study of 692 Egyptian children with type 1 diabetes) declared a prevalence of 4.5% of liver affection [ 26 ]. On the other hand, Farhan et al, reported abnormal hepatic findings in (26%) of children with type 1 diabetes [ 7 ] and ElBaki et al in their study detected 37.3% of cases with NAFLD [ 27 ] . The high prevalence of hepatic affection in our study could be attributed to poorer glycemic control of the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…ElBaky et al concluded that it is essential to do abdominal ultrasound in type I diabetic pediatric patients as an early non-invasive evaluation of liver affection, whereas ARFI is required in more progressive stages [ 27 ]. Moreover, Farhan et al, concluded that NAFLD is significant as an early alarming sign of future result of diabetes mellitus in the form of progression to hepatic fibrosis, cirrhosis and failure [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation